Outdoor Learning-Based Islamic Education: Applying Contextual Learning to Improve Students' Social Skills and Faith - Neng Wina Shalehah (CV. Intake Pustaka, 2025)
This article aims to explore the role of outdoor learning in Islamic education, focusing on how contextual learning can enhance students' social skills and faith. The study investigates how outdoor activities, when integrated into the Islamic curriculum, provide real-world experiences that foster the development of both spiritual values and interpersonal abilities. This study uses a library research approach, analyzing existing literature on outdoor learning, Islamic education, and their impact on social skills and faith development. The research draws on both classical and contemporary studies, examining how Islamic education can benefit from outdoor learning environments and contextual learning strategies. The findings show that outdoor learning can significantly improve students' social skills by offering opportunities for collaborative learning, problem-solving, and interaction with diverse environments. Additionally, these learning experiences align with Islamic teachings, enhancing students' faith and understanding of their role in society. The study suggests that integrating outdoor learning in Islamic education can be an effective strategy to improve students' social interaction, teamwork, and religious understanding. It emphasizes the importance of creating learning environments that extend beyond the classroom to promote holistic development in students, fostering both intellectual and moral growth.